Effects of Iodine Solution on Histopathologic Features of Lead Acetate-Induced Rat Hepar - Prillia, Khalilah; Julizar; Miftah (Rumah Sakit Umum Pusat (RSUP) Dr. M. Djamil, 2024)
Background: Lead is a heavy metal that can be found in the environment. Lead can be naturally occurring or produced from human activities. Lead entering the body can cause oxidative stress which can then cause cell damage. Iodine in the body can act as an antioxidant which then prevents oxidative stress. Methods: This study is an experimental study on 18 Rattus novergicus rats conducted for 19 days. Rats were divided into three groups: negative, positive control group, and treatment group. On the 20th day the rats were killed then the hepatic organs were taken and preparations were made. The preparations were assessed using Knodell’s Score. Data were analyzed using Kruskal-Wallis and then followed by Mann-Whitney Test. Results: The negative control group showed that the dominant is in the form of normal hepatocytes whilst the positive control group hepatic cells experienced cell damage in the form of inflammation, degeneration, and necrosis. In the treatment group, damage to hepatic cells was lower than the positive control group. Conclusion: There is an effect of iodine solution administration in preventing damage to rat hepatic cells induced by lead acetate.